Retained - Inverted - Tooth. A Case Presentation - Virginia Pentón García; Zhenia Véliz Aguila; Ledys Herrera (Medisur)
This research paper presents the case of a 9 year-old male who presented to the Orthodontic Outpatient Department with a clinical absence of the right upper permanent incisive tooth (11). This patient presented with an Angle Class I occlusion , 4 mm projection and two third surpassed crown. X-rays films showed an inverted tooth with its incised border towards the base of the nostrils and a slight flattening of the nostril’s floor at the same side. The patient was referred to the Maxillofacial Surgery Service where he received surgical treatment to get his tooth in the right position. After one year of follow-up the tooth’s root is almost completed and a tooth break out is expected. Its space is kept through orthodontic apparatus